New methods for the quantification of mixed chimerism in transplantation - Picard, Christophe; Frassati, Coralie; Cherouat, Nicem; Maioli, Sandrine; Moskovtchenko, Philippe; Cherel, Mathilde; Chiaroni, Jacques; Pedini, Pascal (Frontiers in Immunology, 2023)
Background: Quantification of chimerism showing the proportion of the donor in a recipient is essential for the follow-up of hematopoietic stem cell transplantation but can also be useful to document an immune tolerance situation after solid organ transplantation. Historically, chimerism has been quantified from genomic DNA, but with technological advances, chimerism from donor-derived cell-free DNA seems particularly relevant in solid organ transplantation. Methods: The reference method was until recently the short tandem repeat technique, but new innovative techniques as digital PCR (dPCR) and NGS, have revolutionized the quantification of chimerism, such as the so-called microchimerism analysis. After a short review of chimerism methods, a comparison of chimerism quantification data for two new digital PCR systems (QIAcuity™ dPCR (Qiagen®) and QuantStudio Absolute Q (ThermoFisher®) and two NGS-based chimerism quantification methods (AlloSeq HCT™ (CareDx®) and NGStrack™ (GenDX®)) was performed. Results: These new methods were correlated and concordant to routinely methods (r²=0.9978 and r²=0.9974 for dPCR methods, r²=0.9978 and r²=0.9988 for NGS methods), and had similar high performance (sensitivity, reproductibility, linearity). Conclusion: Finally, the choice of the innovative method of chimerism within the laboratory does not depend on the analytical performances because they are similar but mainly on the amount of activity and the access to instruments and computer services.